217 Covid-19 And Femoral Neck Fracture: A Retrospective Review. (12th October 2021) - Morris, R; Elbadri, Z; Patel, V; Azam, A
Abstract: Aim: Covid-19 has dominated healthcare over the past year. It most severely affects the elderly, a population whom also commonly present following falls, sustaining femoral neck fractures. Our aim was to retrospectively evaluate the effects of concomitant covid-19 infection in patients presenting acutely with femoral neck fractures. Method: We conducted a retrospective review of all patients with femoral neck fractures during the 'first wave' of the coronavirus pandemic in Ysbyty Gwynedd (Bangor, UK), between April 2020 to June 2020. We noted each patient's covid-19 status within 14 days of presentation with their acute femoral neck fracture and compared length of stay, discharge destination and mortality rate between covid and non-covid groups. Results: There was a total of 75 femoral neck fractures in the 3-month period studied. 4 patients had incomplete data and were excluded from analysis. Of the remaining 71 patients, 15 (21%) were covid-positive within 14 days of admission, 47 patients (66%) were confirmed covid-negative and 9 patients (13%) received no coronavirus testing. The average age of patients was 88 in the covid-positive group and 84 in the covid-negative group. Those who developed covid-19 infection had an increased length of hospital stay (33 days covid-positive versus 14 days covid-negative; p = 0.25) and significantly increased in-hospital mortality rate (47% covid-positive versus 6% covid-negative; p = 0.001). Conclusions: These results show that concomitant infection with covid-19 shortly after femoral neck fracture is associated with a significant increase in hospital mortality. They highlight the importance of trying to prevent covid-19 infection in this patient group.